The Longitudinal Interplay between Bullying, Victimization, and Social Status: Age-related and Gender Differences - Sentse, Miranda; Kretschmer, Tina; Salmivalli, Christina (Social Development, 2015)
The current study examined the longitudinal interplay between bullying, victimization, and social status (acceptance, rejection, and perceived popularity) over the course of 1 year. Cross-lagged path models were estimated for two cohorts, covering grades 3-6 (N = 3904, M age = 11.2 years) and grades 7-9 (N = 4492, M age = 14.4 years). Comparisons between cohorts and by gender were conducted. The results of this study corroborate the complexity of the longitudinal interplay between bullying, victimization, and social status in showing that direction and strength of associations differ by type of peer status, age, and gender. Conclusions cannot be drawn without taking these differences into account. The findings are discussed according to these differences, and directions for future research are provided.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Bullying; Cross-lagged path models; Social status; Victimization